The Impact of High-Performance Work Systems on Confrontation Competitive Challenges and The Role of Managerial Control as Moderating Variable in The Banking System at Dongola Locality in The Northern State of Sudan - Ali, Mashair Hussien Khalifa; AbdelHamid, Mahmoud AbdelMoati Hashem (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to investigate the impact of (HPWS) on (CCC) and the role of (MC) as moderating variables in (BS) at Dongola Locality. The study followed the descriptive analytical method & historical method. The study sample consists of (150) Employees. the study reached a moderating (MC) relationship between (HPWS) and (CCC) in (BS) with a change in the determination coefficient of (0.237). The study recommended activating some practicing that enables (CCC) in branches of banks under study.